Salivary duct carcinoma of the palate - Ponniah I; Murali G; SureshKumar P; Kumaran M; Shaheen A (Wolters Kluwer Medknow Publications, 2005)
Salivary duct carcinoma is a rare high-grade neoplasm that more frequently affects the parotid gland. Though neoplasms of this type are infrequent in minor salivary glands, they are less aggressive and may lead to early diagnosis before distant metastases could occur. Salivary duct carcinoma is also the most frequent epithelial component of carcinosarcoma. The present article reports a case of SDC of the palate in a 26-year-old male and discusses SDC as a malignant epithelial component in carcinosarcoma.